2014
DOI: 10.1016/j.cell.2014.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Age-Dependent Microtubule Acetylation by Tubulin Acetyltransferase

Abstract: Acetylation of α-tubulin Lys40 by tubulin acetyltransferase (TAT) is the only known posttranslational modification in the microtubule lumen. It marks stable microtubules and is required for polarity establishment and directional migration. Here we elucidate the mechanistic underpinnings for TAT activity and its preference for microtubules with slow turnover. 1.35 Å TAT cocrystal structures with bisubstrate analogs constrain TAT action to the microtubule lumen and reveal Lys40 engaged in a suboptimal active sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
208
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(234 citation statements)
references
References 73 publications
11
208
4
2
Order By: Relevance
“…4D). In addition, we found that αTAT1 does not acetylate tubulin dimers as efficiently as it does intact microtubules, consistent with previous αTAT1 studies (18,19) (Fig. 4E, blue).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…4D). In addition, we found that αTAT1 does not acetylate tubulin dimers as efficiently as it does intact microtubules, consistent with previous αTAT1 studies (18,19) (Fig. 4E, blue).…”
Section: Resultssupporting
confidence: 92%
“…However, despite identification of the enzyme and its substrate, the mechanism for how αTAT1 enters the microtubule lumen to access its acetylation sites is yet to be fully understood. There are several potential mechanisms for how αTAT1 may access the acetylation site on the inside of the microtubule lumen: by copolymerization with tubulin at growing microtubule plus-ends (15), by transient openings in the lattice during microtubule breathing (13,16,17), or by microtubule end-entry (12,18). Copolymerization is not likely to be the primary mechanism for αTAT1 access, because stable microtubules are acetylated, and because αTAT1 is more active on polymerized microtubules than on free tubulin dimers (12,13,(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cytoskeleton microtubules are regulated by several types of conserved posttranslational modifications (Song and Brady, 2014). Although the biological meaning of such mechanisms is still poorly understood, it was reported that tubulin acetylation increases its stability and half-life, rendering microtubules more resistant to druginduced depolymerization and disassembly (Matsuyama et al, 2002;Szyk et al, 2014). Previous studies showed that METH impacts actin filaments, leading to actin depolymerization, altered cell shape and local accumulation of condensed actin, which may compromise TJs function and BBB integrity (Park et al, 2013;Young et al, 2014).…”
Section: Discussionmentioning
confidence: 99%